(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the problem of psychological selfrehabilitation of a person in stressful situations and during a life crisis. The essence of the concept of stress was investigated. There has been given stages of development of stressful state and possible causes of its occurrence. Also, has been substantiated reasons for the current trend towards an increase in the number of people with psychological problems. The scientific literature was reviewed regarding the psychology of extreme situations, psychological self-rehabilitation. The methods and techniques proposed by psychologists for dealing with stress and significance of difficulties in a person’s life was analyzed. And also was presented the results of a study regarding the students’ tendency to develop stress.